2017
DOI: 10.1177/0271678x17724681
|View full text |Cite
|
Sign up to set email alerts
|

New astroglial injury-defined biomarkers for neurotrauma assessment

Abstract: Traumatic brain injury (TBI) is an expanding public health epidemic with pathophysiology that is difficult to diagnose and thus treat. TBI biomarkers should assess patients across severities and reveal pathophysiology, but currently, their kinetics and specificity are unclear. No single ideal TBI biomarker exists. We identified new candidates from a TBI CSF proteome by selecting trauma-released, astrocyte-enriched proteins including aldolase C (ALDOC), its 38kD breakdown product (BDP), brain lipid binding prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 121 publications
2
58
0
Order By: Relevance
“…In our study population, correlations between free-circulating and exosomal concentration in serum were strong and improved over time for the two cytoskeletal proteins NFL and GFAP, in contrast to t-tau and especially UCH-L1, which showed weaker correlations that appreciably worsened at the late stages of injury. The most likely interpretation of these findings is that acute glial and neuroaxonal injury results in structural damage leading to (1) ensuing direct leakage of NFL and GFAP into the extracellular space and biofluids through mechanoporation, or altered plasmalemma permeability of injured cells [23][24][25], and (2) intracellular accumulation of aggregated proteins [26] that, in turn, are secreted through an exosome-mediated pathway to reduce toxicity and maintain intracellular proteostasis [21]. Taken together, these observations support the idea that free-circulating and exosomal concentrations of cytoskeletal proteins in serum are products of a common disease-induced damage that follows two distinct parallel pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In our study population, correlations between free-circulating and exosomal concentration in serum were strong and improved over time for the two cytoskeletal proteins NFL and GFAP, in contrast to t-tau and especially UCH-L1, which showed weaker correlations that appreciably worsened at the late stages of injury. The most likely interpretation of these findings is that acute glial and neuroaxonal injury results in structural damage leading to (1) ensuing direct leakage of NFL and GFAP into the extracellular space and biofluids through mechanoporation, or altered plasmalemma permeability of injured cells [23][24][25], and (2) intracellular accumulation of aggregated proteins [26] that, in turn, are secreted through an exosome-mediated pathway to reduce toxicity and maintain intracellular proteostasis [21]. Taken together, these observations support the idea that free-circulating and exosomal concentrations of cytoskeletal proteins in serum are products of a common disease-induced damage that follows two distinct parallel pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Last, some astrocyte proteins like GFAP or their break‐down products may also end up in the cerebrospinal fluid of patients subject to traumatic brain injury [TBI, (Halford et al, )], but also in more progressive diseases like Creutzfeldt‐Jakob disease or AD [for review, see (Carter et al, ; Perez‐Nievas & Serrano‐Pozo, )].…”
Section: Why Bother With Reactive Astrocytes?mentioning
confidence: 99%
“…Such improvements will be facilitated by basic studies that establish the molecular and functional profile of reactive astrocytes (see Section 6) but also of their microglia or neuronal neighbors, allowing the identification of new and specific astrocyte targets. Last, some astrocyte proteins like GFAP or their break-down products may also end up in the cerebrospinal fluid of patients subject to traumatic brain injury [TBI, (Halford et al, 2017)], but also in more progressive diseases like Creutzfeldt-Jakob disease or AD [for review, see (Carter et al, 2019;Perez-Nievas & Serrano-Pozo, 2018)].…”
Section: Why Bother With Reactive Astrocytes?mentioning
confidence: 99%
“…The results from the present study are thus consistent with the aforementioned studies, with an AUC of 0.755 (95%CI 0.628-0.882). It has been suggested that combining several astroglia-derived markers may improve the predictive ability 44 . NF-L has been reported to be a highly sensitive blood-based protein biomarker for severe TBI.…”
Section: Journal Of Neurotraumamentioning
confidence: 99%